1992
DOI: 10.1099/00222615-36-1-46
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibodies in serum of patients with hydatidosis recognised by immunoblotting

Abstract: Summary. Hydatid fluids from sheep, goat, pig and man, after resolution by sodium dodecyl sulphate-polyacrylamide gel electrophoresis under reducing conditions, revealed at least 1 5 discrete polypeptide bands of 8-1 16 Kda. By ELISA, sera from all 20 cases of hydatidosis showed anti-hydatid antibody, but so did 11 (73%) of 15 sera samples from cysticercosis patients, eight (67%) of 12 sera from patients with other parasitic infections (amoebic liver abscess or hymenolepiasis) and one (4%) of 25 sera from heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
7
30
0
1
Order By: Relevance
“…Our ELISA results are similar to those obtained by Zarzosa et al (1999). In our WB, we could not get sensitivity or specificity results higher than 90 % for single bands, despite the high sensitivity and specificity results obtained with antigen 5 or antigen B by others (Kanwar et al, 1992;Sbihi et al, 1997). The discrepancy may be attributed to the differences in using purified antigen or electrophoresis conditions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our ELISA results are similar to those obtained by Zarzosa et al (1999). In our WB, we could not get sensitivity or specificity results higher than 90 % for single bands, despite the high sensitivity and specificity results obtained with antigen 5 or antigen B by others (Kanwar et al, 1992;Sbihi et al, 1997). The discrepancy may be attributed to the differences in using purified antigen or electrophoresis conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Although the most sensitive band in the WB of hepatic CE, according to the ROC curve analysis, is 52-54 kDa, it seems to have little importance, in differentiating pulmonary and hepatic CE. Similarly, despite the relatively high sensitivity of the other bands of intermediate molecular weight (24 kDa, 44-46 kDa) as has been observed by others (Kanwar et al, 1992;Doiz et al, 2001), these bands did not allow differentiation between hepatic and pulmonary CE. Although some authors showed relatively high sensitivity for the 10 to 12 kDa protein, the smallest subunit of the B antigen (Verastegui et al, 1992;Doiz et al, 2001), in our investigation, this band presented lower sensitivity for detection of CE cases.…”
Section: Discussionmentioning
confidence: 66%
“…Some of the products identified in HCF by the pool of human sera in the present study may correspond to those previously described by other authors using the same antigenic extract. This may be the case of the protein of 34 kDa (recently identified by Poretti et al 1999), and the protein of 110 kDa, probably related with the component of 100 kDa described by Shambesh et al (1995), the protein of 110-120 kDa (Shapiro et al 1992), and the protein of 116 kDa (Kanwar et al 1992).…”
Section: Discussionmentioning
confidence: 90%
“…The HCF antigen is prepared as per the method described by KANWAR et al 7 . The HCF is aspirated aseptically from the fertile hydatid cyst and is collected in sterile centrifuge tube.…”
Section: Preparation Of Hydatid Cyst Fluid (Hcf) Antigenmentioning
confidence: 99%